Предмет:
МатематикаАвтор:
анонимПри значениях z1 = -2 + i и z2 = 2 - 6 * i:
1) z1 + z2 = (-2 + i) + (2 - 6 * i) = -5 * i;
2) z1 - z2 = -2 + i - (2 - 6 * i) = -2 + i - 2 + 6 * i = -4 + 7 * i;
3) z1 * z2 = (-2 + i) * (2 - 6 * i) = -4 + 2 * i + 12 * i - 6 * i^2 = -4 + 14 * i - 6 * i^2;
4) z1 : z2 = (-2 + i) : (2 - 6 * i) = (-2 + i)/(2 - 6 * i);
5) z1^2 = (-2 + i)^2 = 4 - 4 * i + i^2;
6) z2^3 = (2 - 6 * i)^3 = 8 - 48 * i + 72 * i^2 - 24 * i + 144 * i^2 - 216 * i^3 = 8 - 72 * i + 216 * i^2 - 216 * i^3.
Автор:
fridacoffeyДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть